The music that I like. (Journal of Parents and Teachers, 2014)
At present, mainly adolescents and young people go on the street listening to music that responds to their personal tastes. This article offers small contributions from young people who explain what music is for them and what musical styles they like best.
Keywords: Contributions; music; youth and adolescence; musical styles.